The uncultivated majority of peat swamp bacterial and archaeal communities - Mohamad Roslan, Muhamad Aidilfitri; Mohamad, Mohd Azrul Naim; Mohd Omar, Suhaila (2018)
Tropical peat swamp forest is well known for huge terrestrial carbon storage through a substantial accumulation of organic, matter mainly derived from vegetation residues, also known as peat. However, limited information on microbial diversity and their ecological function in this environment is available. This research aims to investigate the bacterial and archaeal diversity in the soil of Pekan peat swamp forest via 16S rRNA gene analysis. The amplicon sequencing was performed on a paired-end Illumina HiSeq platform. Results from QIIME analysis of 16S rRNA gene fragments identified 28,480 bacterial and archaeal OTUs. Among others, acidobacteria and proteobacteria dominated the bacterial phyla across all samples with an average relative abundance of 79.46%. In conclusion, this study provides bacterial and archaeal diversity information that served as one of the reference platforms for future ecological and functional studies such as methane accumulation process or lignocellulose biodegradation.